(untitled) (JURNAL ULET (Utility, Earning and Tax), 2024)
This study aims to see and determine the financial performance of Toko Nisa Elektro by using the level of activity ratios and profitability ratios. The research method used is descriptive method. The data collection techniques used are interviews and documentation. This study uses data analysis methods, namely activity ratios (Inventory Tuurnover, Working Capital Turnover, and Total Assets Turnover) and profitability ratios (Net Profit Margin, Return On Assets, and Return On Equity). Based on the results of the study, it is concluded that from the results of the analysis of the effectiveness of asset management, Toko Nisa Elektro is classified as poor because the performance of Toko Nisa Elektro is less effective in managing all of its assets and inventory, and from the results of the analysis of the ability to earn profits, Toko Nisa Elektro is classified as good in generating gross profit and net profit even though it has experienced ups and downs in profits in three periods, namely in 2020-2022. Based on the standard calculation of the financial performance of the profitability ratio, Toko Nisa Elektro has good performance to generate profits